Design and Application of Risk Early Warning System for Subway Station Construction Based on Building Information Modeling Real-Time Model - Qianlong Tang; Mingfeng Lei; Binbin Zhu; Limin Peng; Weimin Wu; Chenghua Shi (Advances in Civil Engineering)
The problems faced by subway stations in the construction process are more complex than those by overground buildings. Therefore, the construction risk for such structures is highly unpredictable and the risk management is difficult. Building information modeling (BIM) technology has strong visualization, simulation, and integration characteristics that make it conducive to the development of a risk early warning system for underground engineering. According to the functional requirements of risk early warning for subway stations, a risk early warning system based on a BIM real-time construction model is designed in this study for a subway station construction. The operation process of the risk early warning system is established through the grey prediction method to propose the operation method of the early warning system. The early warning system is applied to the Xiangjiang New Town Station of Changsha Metro Line 4 in China to verify its feasibility.